The Doorway into Freedom: the Case of the 'Suspected Wife' in Romans 7.1-6 - Rchmann, Luzia Sutter (Journal for the study of the New Testament, 2001)
Most interpreters reflect little on the substance of Rom. 7.2-3, possibly because of parable theories and the difficulty of perceiving the experiential reality of Jews and of women. The term ύπανδρος leads to the sotah, the suspected wife of a jealous husband. It is necessary to investigate the contemporary discussion of the sotah, if we are to understand what Paul says here about the 'law of the husband'. Under the total reign of sin, the husband's death is the only way for the suspected wife to begin a new life. But now Paul perceives the totality of the rule of sin and death as broken, thanks to the resurrection of Christ. He holds the door wide open for the sotah, so that she can leave the position of the accused; and he praises the power of the resurrection which enables everyone to leave the reign of sin behind and start afresh.